Applicability of the Limit Equilibrium Method and the Finite Element Method in Predicting the Stability of Embankment Slopes - Nawarathna, T.H.K.; de Silva, L.I.N. (The Institution of Engineers, Sri Lanka, 2014)
Evaluation of the stability of the embankment slopes is vital to ensure a safe and operational embankment. Stability of embankment slopes can be evaluated by using the available analytical methods or by field monitoring data. The most widely used analytical techniques include the limit equilibrium approach and the finite element approach. This study was carried out to investigate the applicability of the limit equilibrium approach and the finite element approach in predicting the stability of embankment slopes. Two test embankments published in the literature and three embankments, which are belong to the Colombo- Katunayaka highway were analyzed by using the finite element method and the limit equilibrium method and the results have been compared with the field monitoring data. Results of the present study verify that both the finite element method and the limit equilibrium method can predict the stability of the embankment slopes reasonably well. In addition, the finite element method can be used to reasonably estimate the deformations of the embankments as well.
Keywords: Embankment stability; Finite element method; Limit equilibrium method